2016
DOI: 10.1149/2.0061608jss
|View full text |Cite
|
Sign up to set email alerts
|

T-CNTFET with Gate-Drain Overlap and Two Different Gate Metals: A Novel Structure with Increased Saturation Current

Abstract: For the first time, in this paper a tunneling field effect transistor based on semiconductor carbon nanotubes with gate and drain overlap and dual material gate (OVDMG-T-CNTFET) is proposed and simulated using non-equilibrium Green's function (NEGF). This structure uses two metals with different workfunctions. The metal close to source has higher workfunction. This metal controls tunneling at source side of channel and increases ON state current. Drain side impurity penetrates to the channel region or in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…1) and performance 2 (perf. 2) are defined as follows: 11 Performance 1 = Av power consumption [15] Performance 2 = Av * Cutoff frequency [16] Based on these simulation results, the proposed working models for the CNTFET have advantages compared to CNTFET models in Refs. 9-13 in terms of power consumption, drain current, intrinsic gain, transconductance, output conductance, DIBL, subthreshold slop and performances.…”
Section: Simulations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and performance 2 (perf. 2) are defined as follows: 11 Performance 1 = Av power consumption [15] Performance 2 = Av * Cutoff frequency [16] Based on these simulation results, the proposed working models for the CNTFET have advantages compared to CNTFET models in Refs. 9-13 in terms of power consumption, drain current, intrinsic gain, transconductance, output conductance, DIBL, subthreshold slop and performances.…”
Section: Simulations and Discussionmentioning
confidence: 99%
“…To drive out T(E) from these formulas, Wentzel-Kramers-Brillouin (WKB) approximation can be applied to 3. As a result, T(E) is formulated as follows: 16 T If these formulas are used only for source (or drain), then all the effective parameters and their relation to CNTFET's output can be extracted. The resulted formulas can be utilized to simulate CNTFET characteristics.…”
Section: Approachmentioning
confidence: 99%
“…There are various resources introducing graphene as one of the important materials providing fascinating facilities for applications in future nanoscale devices. [7][8][9][10] The authors have considered the other allotrope of carbon as new two-dimensional carbon nanomaterials that are called tetragonalgraphene nanoribbons (TGNRs) which were first suggested by Liu et al 11 According to Liu's research, T-graphene is theoretically demonstrated to be a 2D carbon allotrope which can be metastable and dynamically stable. It is found that T-graphene (TG) with tetragonal symmetry has Dirac-like fermions and a high Fermi velocity like graphene though it has nonequivalent bonds and nonhoneycomb structure.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Therefore, there is a consensus in the community that, MOSFET scaling is approaching to its limits, and it is necessary to introduce new materials, structures and device concepts to continue performance improvement. 1,8,9 For this, to solve aforementioned problems, variety of structures with interesting architectures have been proposed, including FINFET structures, 10 tunnel field effect transistor (TFET) structures, 11 nanowires 12 and ground plane concept 10,13 beside doping engineering in the silicon film, 14 workfunction/dielectric engineering in the gate region 15 and buried oxide (BOX) engineering. 16,17 Graphene, the 2D (two-dimensional) carbon-based material, has attracted significant attention during the past years.…”
mentioning
confidence: 99%